GENDER DISPARITY IN EDUCATION IN KHYBER PAKHTUNKHWA: A CASE STUDY OF DISTRICT BUNER - Muhammad Rasheed; Chusnul Mar’iyah (International Journal of Contemporary Issues in Social Sciences, 2024)
Gender disparities in education remain a major issue in many developing countries, including District Buner in Khyber Pakhtunkhwa, Pakistan. This research looks at the socio-cultural, economic, and structural aspects that lead to gender gaps in schooling in this district. The study takes a mixed-methods approach, combining quantitative surveys and qualitative interviews to give a comprehensive knowledge of the hurdles females encounter in obtaining and finishing their education. The results show that cultural norms such as early marriage and patriarchal views, economic restrictions such as poverty and low financial resources, and poor educational infrastructure all have a negative impact on females’ educational possibilities. The research demonstrates that these discrepancies have an influence on access, enrolment, retention rates, and overall educational quality, further marginalizing females in remote locations. To address these issues, the study suggests enacting gender-sensitive policies, expanding community involvement, enhancing school infrastructure, and giving financial assistance to families. Furthermore, it underlines the need of educational initiatives that promote gender equality and advocate for girls’ access to school. This report proposes a mix of regulatory measures, community-driven efforts, and specialized educational programs to give concrete solutions to reduce and eradicate gender gaps in education in District Buner. The results add to the larger discussion on gender equality in education and emphasize the significance of inclusive measures for Pakistan’s long-term development.